Child Friendly Madrasah: The Role Of The Madrasah Head In Efforts To Prevent Immoral Acts By Teachers Toward Students - Nursita, Dwi Indah (ZAHRA: Research and Tought Elementary School of Islam Journal, 2024)
This study underscores the crucial role of schools in ensuring the safety and comfort necessary for realizing children's rights in education. Focusing on the implementation of Madrasah Ramah Anak (MRA) in MI Almaarif 02 Singosari and MIT Arroihan Lawang, the research highlights the Madrasah Head's pivotal role in preventing teacher abuse against students. Both madrasas have effectively implemented MRA, meeting indicators without discrimination or violence. The Madrasah Head, functioning as an educator, manager, administrator, innovator, motivator, supervisor, and leader, has successfully executed these roles. Actively involved in declaring the madrasah child-friendly, organizing MRA training, issuing regulations, and overseeing teachers, the Madrasah Head ensures a safe environment through initiatives such as anti-bullying ambassadors and a supervisory system. Beyond an administrative figure, the Madrasah Head actively contributes to fostering a child-friendly school culture, showcasing commitment to student safety. Overall, the research offers a positive overview of the Madrasah Head's central role in safeguarding children's rights and fostering a supportive educational environment for optimal student development.